Identification of Soil Organic Nitrogen Substance Acting as Indicator of Response of Cocoa Plants to Nitrogen Fertilizer - John Bako Baon (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2008)
An indicator needed for estimating the presence of response of cocoa (Theobroma cacao) trees to nitrogen (N) fertilizer has been well understood, however there is still little progress on the work on identification of organic N fraction which regulates the response of cocoa to N fertilizer. The objective of this study is to identify a fraction of soil organic N which is very closely related with degree of cocoa response to N fertilizer. Hydrolyses were performed on soil samples derived from 23 sites of cocoa plantations distributed both in Banyuwangi district (12 sites) and in Jember district (11 sites). Analysis of organic N fractions consisted of total hydrolysable N, ammonium N, amino sugar N, amino acid N and combinations of those fractions. To investigate the level of cocoa plants response to N fertilizer, seedlings of cocoa were planted in plastic pots treated with and without urea as source of N. Degree of response of cocoa plants to N fertilizer was measured based on growth parameters, such as plant height, leaf number, stem girth, fresh weight of stem, leaf and shoot; and dry weight of stem, leaf and shoot. Results of this study showed that biggest response of cocoa was shown by dry weight of leaf at the level of 29,22% (in the range of -17,43% – 95,98%), whereas the smallest response was shown by stem dry weight at the level of -1,04 (in the range of -26,16 – 47,54). From those of organic N fractions analyzed, only N ammonium did not show any significant correlations with all the growth parameters observed. Leaf dry weight was the most closely related parameter with nearly all organic N fractions followed by shoot dry weight and stem girth. The soil organic N fraction which had very significant relation with cocoa plant response was total hydrolysable N. Using the method of Cate-Nelson, it was revealed that cocoa gardens contain total hydrolysable N less than 1273 mg/kg were classified as responsive to N fertilizer.Key words: plant response, Theobroma cacao, soil organic nitrogen, N fertilizer, soil testing, fertilization, soil variability, soil hydrolysis